Structure System For Flood Disaster Emergency Shelter On Peatlands With A Parametric Approach - Stephanus Evert Indrawan; Lya Dewi Anggraini; Rendy Iswanto (Eduvest - Journal of Universal Studies, 2022)
Kalimantan Island has had minimal risk of flooding, but this condition has changed due to extreme natural damage. As a result, in 2021, many provinces were affected by floods. One example is the province of South Kalimantan. The Center for Disaster Information and Communication of the National Disaster Management Agency (BNPB) released on January 17, 2021, ten districts/cities affected by flooding in South Kalimantan Province, namely Tapin Regency, Banjar Regency, Banjar Baru City, Tanah Laut City, Banjarmasin City, Hulu Sungai Regency Central, Balangan Regency, Tabalong Regency, South Hulu Sungai Regency, and Batola Regency. Eighteen thousand two hundred twenty-two people were displaced due to flooding. These victims were spread across six regencies/cities, namely the cities of Banjarmasin, Banjarbaru, Banjar Regencies, Tanah Laut, Barito Kuala, and Hulu Sungai Tengah. Therefore, the local government is trying to provide emergency shelter after the flood. However, post-disaster needs are very complex in the process, such as the character of peatlands that require special structural knowledge to build them, the difficulty of access during disasters, the lack of availability of building materials in disaster conditions, and the high demand for housing. To answer the need for multi-parameters in the process of designing unloading structures for post-flood emergency shelters, a parametric approach is needed that will significantly change the design approach such as testing several parameters at once, controlling the dimensions-quality-quantity of materials, being able to perform analysis and simulation tests in one flow—integrated work.